2019
DOI: 10.3389/fpls.2018.01927
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster of MYB Transcription Factors Regulates Anthocyanin Biosynthesis in Carrot (Daucus carota L.) Root and Petiole

Abstract: Purple carrots can accumulate large quantities of anthocyanins in their roots and –in some genetic backgrounds- petioles, and therefore they represent an excellent dietary source of antioxidant phytonutrients. In a previous study, using linkage analysis in a carrot F2 mapping population segregating for root and petiole anthocyanin pigmentation, we identified a region in chromosome 3 with co-localized QTL for all anthocyanin pigments of the carrot root, whereas petiole pigmentation segregated as a single domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 45 publications
6
70
1
1
Order By: Relevance
“…Three QTLs associated with variations in Cy3XSGG in carrots have been proposed previously (Cavagnaro et al , ). Q1 is located in the same region as DcMYB7 , a gene related to anthocyanin biosynthesis in carrots with a purple root and petiole (Iorizzo et al , ). A UCGXT and a SAT gene , namely DcUCGXT1 and DcSAT1 , with the best BLAST match to UGT79B1 and SAT (At2g23000) from Arabidopsis (Montefiori et al , ), was found within the Q3 and Q2 locus, respectively (Xu et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three QTLs associated with variations in Cy3XSGG in carrots have been proposed previously (Cavagnaro et al , ). Q1 is located in the same region as DcMYB7 , a gene related to anthocyanin biosynthesis in carrots with a purple root and petiole (Iorizzo et al , ). A UCGXT and a SAT gene , namely DcUCGXT1 and DcSAT1 , with the best BLAST match to UGT79B1 and SAT (At2g23000) from Arabidopsis (Montefiori et al , ), was found within the Q3 and Q2 locus, respectively (Xu et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous report, we identified DcMYB6 , an R2R3‐MYB gene involved in carrot root anthocyanin biosynthesis within the P 3 region (Xu et al , ). Iorizzo et al identified an R2R3‐MYB gene, DcMYB7 , within the P 3 region as a candidate for the gene controlling anthocyanin biosynthesis in carrot with a purple root and petiole (Iorizzo et al , ). Recently, we confirmed that DcMYB7 is P 3 (Xu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, purple carrot root pigmentation extensively varies across different carrot genotypes, ranging from the purple peridermal carrot type (purple periderm but nonpurple phloem and xylem) to the solid purple carrot type (purple periderm, phloem, and xylem). The genetic control of anthocyanin pigmentation in purple carrots has been investigated (Simon, 1996;Yildiz et al, 2013;Cavagnaro et al, 2014;Xu et al, 2014Xu et al, , 2016Xu et al, , 2017Kodama et al, 2018;Iorizzo et al, 2019). Two genes that condition the anthocyanin pigmentation of carrot roots from different genetic backgrounds, P 1 and P 3 , have been identified and genetically mapped within 28.2-and 12-centimorgan regions, respectively, on chromosome 3, supporting the theory of two independent mutation and human selection events during the domestication of purple carrots (Cavagnaro et al, 2014).…”
mentioning
confidence: 77%
“…DcMYB6, corresponding to DCAR_000385 in the carrot genome, encodes an R2R3-MYB that can induce anthocyanin biosynthesis in Arabidopsis (Arabidopsis thaliana; Xu et al, 2017). Very recently, DcMYB6 was anchored to the P 3 region (Iorizzo et al, 2019). Using phylogenetic analyses, these authors also identified five additional MYB transcription factors of the anthocyanin biosynthesis-related subgroup of MYBs, DcMYB7 (DCAR_010745), which was designated DcMYB113-like in the carrot genome (Iorizzo et al, 2016), DcMYB8 (DCAR_010746), DcMYB9 (DCAR_010747), DcMYB10 (DCAR_010749), and DcMYB11 (DCAR_010751), within the P 3 genomic region (Iorizzo et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation